Relationship between dislocations and misfit strain relaxation in InGaAs/GaAs heterostructures. Issue 1 (30th November 2016) - Li, Jinping; Miao, Guoqing; Zeng, Yugang; Zhang, Zhiwei; Li, Dabing; Song, Hang; Jiang, Hong; Chen, Yiren; Sun, Xiaojuan; Li, Zhiming
Abstract : Every 60° dislocations glide and react to form a 90° dislocations. The 90° dislocations would be split into 60° dislocation pairs when they suffer great strain. The decomposition of 90° dislocations is far less effective than the former 90° dislocation array in strain relaxation. Abstract : Large lattice mismatched heterostructures In0.78 Ga0.22 As/GaAs were grown with a low-temperature (LT) InGaAs buffer. Misfit dislocation arrays were observed at the LT-buffer/GaAs interfaces. Transmission electron microscopy (TEM) was used to investigate the microstructures of the heterointerfaces. The relationship between misfit dislocations and strain relaxation at the interface was analysed. It was found that strain redistribution gives rise to the discrepancy of interfacial structure and misfit strain relaxation for different samples. The experimental results are in favor of the conclusion and confirm the analysis we proposed.